STUDY OF RELIGIOUS COURT JUDGES' DECISIONS ON POLYGAMY PERMITS REVIEW OF DECISION NUMBER 1749/Pdt.G/2018/Pa. Tbn AND DECISION NUMBER 2012/Pdt.G/2024/PA.Sby: STUDI PUTUSAN HAKIM PENGADILAN AGAMA TERHADAP IZIN POLIGAMI KAJIAN PUTUSAN NOMOR 1749/Pdt.G/2018/Pa. Tbn DAN PUTUSAN NOMOR 2012/Pdt.G/2024/PA.Sby - CHOIROTUNNISAH, FADILATIN (Asosiasi Dosen Hukum Acara Perdata (ADHAPER), 2025)
The purpose of this study is to examine the differences in the judges' considerations in Decision Number 1749/Pdt.G/2018/PA.Tbn and Decision Number 2012/Pdt.G/2024/PA.Sby regarding polygamy requests based on high sexual desire. This research is normative in nature, using a legislative and case-based approach. The results of the research show that the judge in Decision Number 1749/Pdt.G/2018/PA.Tbn rejected the petition because the alternative requirements of Article 4 paragraph (2) and the cumulative requirements of Article 5 paragraph (1) were not met. The judge interpreted extensively that the wife's obligations were not limited to serving biological needs, and the petitioner's income was deemed insufficient. Conversely, in Decision Number 2012/Pdt.G/2024/PA.Sby, the petition was granted because the requirements of Article 4 paragraph (2) and Article 5 paragraph (1) were deemed to have been met. The judge made a teleological interpretation and assessed that the petitioner was financially capable and had met the requirements. The majority opinion of scholars regarding court decisions that reject or grant polygamy petitions is that some scholars allow polygamy as an alternative for men who have a strong desire, provided that they are fair and provide sufficient financial support, while some scholars do not allow polygamy if it is done for the reason of having a high biological desire but without a clear purpose. This disparity in decisions is due to legislation and requirements that originate from the judge himself.